The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2105/ajph.2013.301556
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Beverage Consumption and Caloric Intake Among US Adults, Overall and by Body Weight

Abstract: Overweight and obese adults drink more diet beverages than healthy-weight adults and consume significantly more solid-food calories and a comparable total calories than overweight and obese adults who drink SSBs. Heavier US adults who drink diet beverages will need to reduce solid-food calorie consumption to lose weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 22 publications
(20 reference statements)
7
60
2
Order By: Relevance
“…Finally, the interaction between BMI and diet drink intake noted in our analysis is an interesting finding that bears further investigation, especially given other recent data that highlight the role of body weight in this setting. 31 Limitations of this study include its observational nature, and the fact that it involved retrospective analysis of data not collected expressly for the purpose of this paper. It also involves a specific population, that of post-menopausal women, and thus may not be generalizable to other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the interaction between BMI and diet drink intake noted in our analysis is an interesting finding that bears further investigation, especially given other recent data that highlight the role of body weight in this setting. 31 Limitations of this study include its observational nature, and the fact that it involved retrospective analysis of data not collected expressly for the purpose of this paper. It also involves a specific population, that of post-menopausal women, and thus may not be generalizable to other populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent prospective, experimental studies corroborate this finding 29,30,31,32,33,34 , and the possible unhealthy effects of diet soft drinks have been discussed, in addition to a lack of consensus on their safety to drink 35,36 .…”
Section: S152mentioning
confidence: 99%
“…In addition, the hypothesis that artificial sweeteners may increase craving for sweets and energy-dense foods 30,33,38,39,40,41 was raised. Therefore, the association, between diet soft drink intake and overweight seems plausible beyond reverse causality.…”
Section: S152mentioning
confidence: 99%
“…Collison et al [5] showed positive link between uptake of sugary drinks and both indicators (BMI and W_C). In a large cross-sectional study (~24,000 US citizens) indicated that 19% of overweight and 22% of obese participants consume diet beverages [30]. It also found that obese and overweight adults who drink diet drinks tended to have more food [30].…”
Section: Discussionmentioning
confidence: 99%
“…In a large cross-sectional study (~24,000 US citizens) indicated that 19% of overweight and 22% of obese participants consume diet beverages [30]. It also found that obese and overweight adults who drink diet drinks tended to have more food [30]. Researches of this study offered two possible hypothesis; sugar-free drinks still stimulate the mind's "sugar reward" pathways, thus, it causes the person to snack more since he has a "sweet tooth" [30]; and the person might simply transfer the energy uptake he used to have from beverages to increase food consumption [30].…”
Section: Discussionmentioning
confidence: 99%